Understanding torture - Wisnewski, Jeremy (Edinburgh : Edinburgh University Press, 2010)
Despite Victor Hugo's 19th-century proclamation that torture no long er exists, we still find it even now, even in those nations that claim to be paradigms of civility. Why is it that torture still exists in a w orld where it is routinely regarded as immoral? Is it possible to elimi nate torture, and if so, how? What exactly does it mean to call somethi ng 'torture', and is it always morally reprehensible? Arguments in fav our of torture abound, but in this book, the author examines and explai ns the moral dimensions of this perennial practice, paying careful atte ntion to what lessons torture can teach us about our own moral psycholo gy. By systematically exposing the weaknesses of the dominant arguments for torture, drawing on resources in both analytic and continental phi losophy and relevant empirical literature in psychology, he aims to pro vide an over-arching account of torture: what it is, why it is wrong, a nd why even the most civilized people can nevertheless engage in it.
The persistence of torture : an affliction that won't go away -- The history of torture : a sketch -- The wrongness of torture : identifyin g torture's unique despicability -- How torture unmakes worlds -- Think ing through torture's temptations, part one : arguments for torture -- Thinking through torture's temptations, part two : arguments against to rture -- The psychology of torture -- The politics of torture : Orwelli an themes in the Bush League -- Hope amid pessimism : concluding reflec tions on ending torture.
Includes bibliographical references (p. 239-259) and index.
Keywords: Torture -- Moral and ethical aspects